Changing Behaviour: Blindness to Risk and a Critique of Tobacco Control Policy in China-A Qualitative Study - Tong Pei; Tingzhong Yang (MDPI AG, 2022)
(1) Background: It is well recognised that a focus on changing behaviour remains a dominant and often appealing approach to develop health policies. This study provides a sociological insight into young adults' knowledge of the health effects of smoking cigarettes. We also examine the challenges in tobacco control and criticize the implementation policies in Chinese context. (2) Methods: The study applies both a micro-sociological and a macro-sociological approach using semi-structured interviews and documents as the primary research methodology. Fieldwork was conducted from July to September 2016 and December 2016 to March 2017. The qualitative study involved 45 semi-structured interviews with young adults aged 16-24 years (15 females and 30 males) in Tianjin, China. A grounded theory approach was used for a thematic analysis. (3) Results: The participants knew cigarettes are harmful, although they lacked a comprehensive understanding of the health risks of smoking. Because the health consequences usually emerge after a long period of smoking, young smokers decide to take the health risk. All participants have a general understanding of China's tobacco control policies and think that the implementation is ineffective. (4) Conclusions: Changing in smoking is a process embedded in complex social environments and cultures. Smoking behaviour is not only a personal choice, but also related to personal connections with peers and identity in Chinese society. The Chinese government has made significant achievements in tobacco control since joining the WHO framework convention on tobacco control in 2005. However, implementation needs to be stricter in order to achieve international levels of control, especially in taxes on tobacco product and the price of cigarettes. There is an urgent need for the regulation of e-cigarettes in China.